German Students Abroad - Kercher, Jan; Rohde, Nicole (International Higher Education, 2014)
Increasing the number of German graduates who have spent time abroad during their studies is a key objective of Germany's higher education policy. Available data shows that the development of internationally mobile German students depends on the type of mobility, i.e. degree or credit mobility. While there has been a marked increase in degree mobility since 1991, credit mobility quotas have stabilized at about a third of all German graduates since 2000. Thus, Germany has surpassed the Europe-wide target which states that 20% of all graduates should spend a study or training period abroad by 2020. Meanwhile, the Joint Science Conference (GWK) of the federal and state governments considers 50% of graduates who gained study-related experience abroad as a mid-term goal.